A role of actin-regulatory proteins in the formation of needle-shaped spores in the filamentous fungus Ashbya gossypii - Lickfeld, Manuela (2012)
Spore formation is an essential step in the fungal life cycle that contributes to the dispersal of the organism and also to survival under harsh environmental conditions. The morphology of spores shows an astonishing diversity in the fungal kingdom and varies from very simple round and small spores to very complex multi-armed or sigmoid structures. With exception of the regulation of ascospore formation in Saccharomyces cerevisiae and Schizosaccharomyces pombe, which are well-characterized model organisms for spore development in fungi, little is currently known about the regulation of more complex spore morphologies. In this study, the filamentous ascomycete Ashbya gossypii is used as a model system for the investigation of a complex and composite spore morphology. A. gossypii produces linear, needle-shaped spores possessing a length of 30 µm, which can be divided into three major segments: a rigid tip segment, a more fragile membrane compartment and a stable tail-cap. Furthermore, the different compartments were shown to correlate with distinct materials. While the tip segment and the tail-cap of the spores consist of stabilizing materials like chitin and chitosan, these materials are absent from the compartment in the middle. The actin cytoskeleton plays an essential role in several steps of spore formation in A. gossypii. Different regions of actin accumulation were identified that directly correlate with the developing spores. Especially the developing tip segment is characterized by heavy-bundled linear actin structures. Furthermore, proteins of the formin family, a class of actin organizing proteins, were identified to be directly involved in spore formation in A. gossypii. The formin AgBnr2 fulfills an actin-related key function during spore development by linking actin to the spindle pole body during sporulation. Downregulation of AgBNR2 leads to severe sporulation defects, indicating a central function in spore development. Moreover, AgBni1, another representative of the formin family, also has a regulatory function in size determination of the typical needle-shaped spores of A. gossypii. Using a modified yeast two-hybrid approach, four potential activators of the formin AgBni1 were identified: the Rho-type GTPases AgRho1a, AgRho1b, AgRho3 and AgRho4. The interaction of AgBni1 with the two Rho1 GTPases plays an important role during spore development. In this study, the Rho binding domain of AgBni1 was further examined to identify amino acids that are essential for the interaction with the Rho-type GTPases. Using random mutagenesis combined with a two-hybrid screen, the point mutation S250P in the Rho binding domain of AgBni1 was identified to reduce the interaction of the formin with the Rho1 GTPases. Integration of AgBni1 S250P causes an increase in spore length, suggesting a direct effect of this signaling pathway in spore length determination. An actin-regulating protein network that includes the formin AgBni1, the Rho-type GTPases AgRho1a and AgRho1b and the paxillin-like protein AgPxl1 was identified to be mainly involved in the regulation of the spore length. Thereby, this network seems to be involved in the arrangement of the different spore compartments via the actin cytoskeleton.